Identification and evaluation of vaccine candidate antigens from the poultry red mite (Dermanyssus gallinae). Issue 13 (November 2015) - Bartley, Kathryn; Wright, Harry W.; Huntley, John F.; Manson, Erin D.T.; Inglis, Neil F.; McLean, Kevin; Nath, Mintu; Bartley, Yvonne; Nisbet, Alasdair J.
Graphical abstract: Highlights: Ten poultry red mite vaccine candidate antigens were identified and recombinant versions produced. Mite mortality was monitored after feeding on the blood from vaccinated hens. A ⩾1.6-fold increased risk of mite death was observed with four of the vaccine candidates ( P  < 0.001). Best candidates include: a serpin, vitellogenin, hemelipoglycoprotein and a novel protein. Abstract: An aqueous extract of the haematophagous poultry ectoparasite, Dermanyssus gallinae, was subfractionated using anion exchange chromatography. Six of these subfractions were used to immunise hens and the blood from these hens was fed, in vitro, to poultry red mites. Mite mortality following these feeds was indicative of protective antigens in two of the subfractions, with the risks of mites dying being 3.1 and 3.7 times higher than in the control group ( P  < 0.001). A combination of two-dimensional immunoblotting and immunoaffinity chromatography, using IgY from hens immunised with these subfractions, was used in concert with proteomic analyses to identify the strongest immunogenic proteins in each of these subfractions. Ten of the immunoreactive proteins were selected for assessment as vaccine candidates using the following criteria: intensity of immune recognition; likelihood of exposure of the antigen to the antibodies in a blood meal; proposed function and known vaccine potential of orthologous molecules. Recombinant versions of each of these 10 proteins were produced in Escherichia coli and were used to immunise hens. Subsequent in vitro feeding of mites on blood from these birds indicated that immunisation with Deg-SRP-1 (serpin), Deg-VIT-1 (vitellogenin), Deg-HGP-1 (hemelipoglycoprotein) or Deg-PUF-1 (a protein of unknown function) resulted in significantly increased risk of mite death (1.7–2.8 times higher than in mites fed blood from control hens immunised with adjuvant only, P  < 0.001). The potential for using these antigens in a recombinant vaccine is discussed.